2002
DOI: 10.1055/s-2002-23193
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Biosynthesis of DHEA from Cholesterol by First-Trimester Human Placental Tissue: Source of Androgens

Abstract: With a view to establishing whether first-trimester human placentas possess the ability to synthesize DHEA from cholesterol, homogenates of this tissue obtained from two groups of women undergoing elective termination of normally progressing pregnancy between 10 - 12 weeks gestation (n = 5, age 23 - 29 years and n = 5, age 21 - 27 years) were incubated separately with [26-(14)C]cholesterol for the generation of [14C]isocaproic acid + pregnenolone and [7n-3H]pregnenolone for the biosynthesis of [3H]DHEA. Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Historically, most studies have reported a diminished CYP17 activity in the human placenta, except for two reports from the 1960s (11,12) and most recently by Loganath et al (13), who also reported pregnenolone to DHEA conversion in fetal chorion (14) and amnion (15). We were able to demonstrate that isolated midterm human placental cells as well as JEG-3 choriocarcinoma cells are capable of synthesizing estrogens de novo without the addition of androgen precursors to the media.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, most studies have reported a diminished CYP17 activity in the human placenta, except for two reports from the 1960s (11,12) and most recently by Loganath et al (13), who also reported pregnenolone to DHEA conversion in fetal chorion (14) and amnion (15). We were able to demonstrate that isolated midterm human placental cells as well as JEG-3 choriocarcinoma cells are capable of synthesizing estrogens de novo without the addition of androgen precursors to the media.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse side effects have been limited to oily skin, rarely mild acne vulgaris and mild hair loss. Since first-trimester placenta produces DHEA (Loganath et al, 2002), maternal DHEA exposure at moderate dosages in very early pregnancy should not constitute significant risk.…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, DHEA and DHEAS have immunoregulatory actions on the maternal immune system (Nieschlag et al 1974;Facchinetti et al 1986;Tagawa et al 2004). Not only maternal adrenal glands (Nieschlag et al 1973) but also early placenta and fetal adrenal glands are capable of converting cholesterol to pregnenolone to DHEA (Loganath et al 2002). Therefore, serum DHEA suppresses immune reactions by modifying cytokine levels and thus contributing to the development of gestation (Nieschlag et al 1974;Du et al 2001;Tagawa et al 2004).…”
Section: Introductionmentioning
confidence: 99%